Key body posture characteristics of short-distance speed skaters at the start based on artificial intelligence - Xueliana, Z.; Yingjieb, F.; Hang, L. (arXiv e-print repository, 2025)
Objective To conduct biomechanical analysis on the starting technique of male short-distance speed skating athletes in China and determine the key factors affecting the effectiveness of the starting movement.